2004
DOI: 10.4049/jimmunol.173.10.6427
|View full text |Cite
|
Sign up to set email alerts
|

The Class A Macrophage Scavenger Receptor Attenuates CXC Chemokine Production and the Early Infiltration of Neutrophils in Sterile Peritonitis

Abstract: The macrophage scavenger receptor (SR-A) is a multifunctional receptor that is associated with several important pathological conditions, including atherosclerosis. In this study, we show, using a sterile peritonitis model, that it can regulate the inflammatory response. SR-A null mice display an increased initial granulocytic infiltration because of overproduction of the CXC chemokines, MIP-2 and keratinocyte-derived cytokine. This differential response is dependent upon particle internalization and can be mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 33 publications
5
41
0
1
Order By: Relevance
“…Moreover, 129Sv and CD204Ϫ/Ϫ mice examined at 1 and 4 wk postexposure of silica showed neither differences in the accumulation of inflammatory cells nor any appreciable increase in collagen deposition in either strain of mice (data not shown), indicating that the accumulation of inflammatory cells in CD204Ϫ/Ϫ mice occurs over time. These data are consistent with a recent report demonstrating increased infiltration of neutrophils in CD204-deficient mice in response to thioglycollate peritonitis (12). It has been suggested that fibrosis begins as an inflammatory reaction with infiltration of various cell types followed by the enhanced production of cytokines (8,36).…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, 129Sv and CD204Ϫ/Ϫ mice examined at 1 and 4 wk postexposure of silica showed neither differences in the accumulation of inflammatory cells nor any appreciable increase in collagen deposition in either strain of mice (data not shown), indicating that the accumulation of inflammatory cells in CD204Ϫ/Ϫ mice occurs over time. These data are consistent with a recent report demonstrating increased infiltration of neutrophils in CD204-deficient mice in response to thioglycollate peritonitis (12). It has been suggested that fibrosis begins as an inflammatory reaction with infiltration of various cell types followed by the enhanced production of cytokines (8,36).…”
Section: Discussionsupporting
confidence: 82%
“…3D), providing further support for the notion that SR expression does not promote the production of NF-kB-dependent pro-inflammatory cytokines [8,20]. Taken together, these data suggests that class A SR-deficiency results in increased production of IL-10 after LPS stimulation, adding to the evidence that these receptors affect cellular signalling pathways [21][22][23][24].Natural and induced anti-LPS IgM production is increased in class A SR-deficient mice MARCO and SR-A are constitutively expressed on peritoneal and splenic MZ macrophages, being therefore in close contact with innate B1 and MZ B-cell subsets. These two B-cell subsets are producers of natural IgM and they also rapidly produce neutralizing Ab against blood-borne bacterial and viral pathogens at early stage of infection [13,25].…”
supporting
confidence: 57%
“…4 and 5) resulted in enhanced expression and function of the scavenger receptor SR-A. Previous studies reported independent roles for SR-A in clearance of S. aureus and control of chemokine-driven neutrophil recruitment in the peritoneal cavity (55,56). The role of SR-A in pulmonary clearance of S. aureus is not known.…”
Section: Expression Of Sr-a Is Required For Effective Clearance and Cmentioning
confidence: 92%
“…On the other hand, the present findings show that SR-A controls neutrophil recruitment through secretion of the chemokine KC. An earlier study on sterile peritonitis revealed that SR-A regulates the rate of neutrophil chemotaxis through downmodulation of neutrophil chemokines, including KC (55). Inappropriate levels of KC during infection, however, may counteract TNF␣ priming of neutrophil bactericidal activities.…”
Section: Cd11cmentioning
confidence: 99%